2015
DOI: 10.3384/ecp15118419
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modelling of a Flat-Plate Solar Collector for Control Purposes

Abstract: Two different dynamic models of a flat-plate solar collector have been developed in the Modelica language under Dymola ® software. These models have been developed within the Ambassador Project (Onillon, 2014). In this project, models of district heating components are conducted for control purposes, including a solar plant model. The present article describes in detail each of these models along with the development process (e.g., assumptions taken into account). The model validation process and results are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…compared a simple collector model with a more detailed model and measurement data. They concluded that a simple model, like the one developed for this study, is well suited for system analysis [46].…”
Section: Solar Collector Modelmentioning
confidence: 90%
“…compared a simple collector model with a more detailed model and measurement data. They concluded that a simple model, like the one developed for this study, is well suited for system analysis [46].…”
Section: Solar Collector Modelmentioning
confidence: 90%